Microbiologic analysis of 140 patients undergoing revision total knee arthroplasty due to periprosthetic joint infection and aseptic loosening: droplet digital PCR analysis - Xiao-Kai Liu; Heng-Xin Zhao; Lan-Feng Ding; Yuan-He Wang; Shao-Qi Tian (Journal of Orthopaedic Surgery and Research)
Abstract Objective The primary reasons for postoperative joint prosthesis revision after total knee arthroplasty (TKA) are periprosthetic aseptic prosthesis loosening and joint infection (PJI). The objective of this study is to analyze the predominant microbial species responsible for PJI while also discussing was related. Methods A retrospective analysis was conducted on patients who underwent TKA revision surgery for the treatment of PJI and aseptic loosening of joint prostheses at our institution. Patients with aseptic loosening of the prosthesis are group A (n = 68), and patients with PJI are group B (n = 72). The fluid obtained after ultrasonic treatment was then subjected to microbial culture. Droplet Digital PCR (ddPCR) analysis was employed for DNA detection. Results In our study, we included a total of 140 patients divided into groups A (patients with aseptic loosening of the prosthesis) and B (patients with PJI). The microbial culture results showed that 30 patients (45.45%) had Staphylococcus aureus infections, and 24 patients (36.36%) had methicillin-resistant Staphylococcus aureus (MRSA) infections in group B. The DNA testing results revealed that 54.41% (n = 37) of Group A patients still had microbial infections, including both Gram-positive and Gram-negative species. Notably, these patients showed negative microbial cultures but positive DNA detection. Among them, 83.78% (n = 31) had Gram-negative infections, while 16.22% (n = 6) had Gram-positive infections. In Group B, 66 patients (91.67%) had predominantly Gram-positive infections. Conclusion This study innovatively employed ddPCR for DNA detection and microbiologic analysis in 140 patients undergoing revision total knee arthroplasty due to periprosthetic joint infection and aseptic loosening, showed that most patients with PJI mainly affected by infections caused by high-virulence Gram-positive microbe, especially Staphylococcus aureus and MRSA. On the other hand, patients with aseptic loosening of the prosthesis may be associated with a history of multiple low-virulence microbial infections, primarily involving Gram-negative bacteria.